DEVELOPING THE PRAGMATIC COMPETENCE OF FOREIGN LEARNERS: GUIDELINES TO USING CONSTATIVES IN MODERN ENGLISH DISCOURSE - Viktoriia Berezenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article is devoted to the problems of foreign language education in linguistic universities, namely to acquiring the pragmatic competence by students. The research questions whether EFL learners are pragmatically competent in using language in a certain communicative situation. The experimental teaching session proves that the special research methods (descriptive, pragmatic, performative analyses) and divergent forms of learning the modal perspective of constatives in discourse can provide students with the appropriate knowledge base. The main conclusions drawn from this research are that EFL learners can have only elementary pragmatic competence without a special training session. Therefore the current study suggests the procedure of training the communicative skills in the appropriate use of constatives in the process of social interaction with the aim of developing the pragmatic competence of students and helping them acquire their proficiency in achieving certain goals in communication.